Metastatic Primary Breast Leiomyosarcoma in Men: A Case Report - Milan, Joelle; Jradi, Ahmad; Azar, Anthony; Matta, Clemence; Elias, Bachir (Archives of Case Reports, 2025)
Introduction: Breast malignancy is the second most common cancer world widely. Many subtypes exist including carcinomas (most common) and sarcomas (least common). In this case report we discuss a rare case of primary breast leiomyosarcoma in a male patient. Case report: A 94 years old male patient presented for a rapidly evolving right breast mass. Imaging showed a hypoechoic breast mass. Thoracoabdominal CT scan revealed lung and liver lesions. Biopsies confirmed the presence of a primary breast leiomyosarcoma with metastasis to the liver and the lungs. Discussion: Breast leiomyosarcoma is considered to be one of the rarest breast cancers with very few cases reported. The non-specific imaging pattern of this pathology makes histopathologic and histochemical analysis the basis of definitive diagnosis (mitotic features, necrosis, differentiation, S100, cytokeratin, desmin, SMA). Surgery with negative margin is the standard treatment for non-metastatic cases whereas palliative chemotherapy is for metastatic ones. No data on an improved prognosis or survival rate with post-operative chemo/radiotherapies. Conclusion: Further detailed studies on this particular rare type of breast sarcoma are needed to establish gold standard treatment guidelines. Every contribution to the literature can help sharpen our knowledge and understanding of this entity.